Application of Baylis-Hillman methodology in the direct construction of chromone derivatives. Issue 3 (21st January 2016) - Faridoon,; Olomola, Temitope O.; Klein, Rosalyn; Kaye, Perry T.
Abstract: Pyridinium chlorochromate oxidation of Baylis-Hillman-derived tert -butyl 2 H -chromene-3-carboxylates affords chromone-3-carboxylate esters, providing the first application of Baylis-Hillman methodology in a direct and convenient three-step synthesis of chromone derivatives. Graphical abstract: